2013
DOI: 10.3109/08916934.2013.832220
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of perinatal bisphenol A exposure in a mouse model of multiple sclerosis

Abstract: Multiple sclerosis (MS) is a complex disease influenced by genetic and environmental contributing factors. Endocrine disrupting compounds (EDCs) such as bisphenol A (BPA) affect gene expression and hormone-regulated systems throughout the body. We investigated the effects of BPA on Theiler's-virus induced demyelination (TVID), a mouse model of MS. Perinatal BPA exposure, combined with viral infection, resulted in a decreased level of viral antibodies, accelerated the onset of TVID symptoms, increased inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 71 publications
2
13
0
1
Order By: Relevance
“…We note a corroborative report that SJL mice exposed to BPA during gestation and through the mother's milk during lactation had accelerated onset of clinical signs after infection at 4 wk of age with Theiler's virus, which produces CNS inflammation (38). At 20 wk postinfection, the degree of inflammation in the spinal cord was higher in BPA-exposed compared with vehicle treatment; no sex differences in the degree of inflammation were noted in the BPA mice.…”
Section: Discussionsupporting
confidence: 66%
“…We note a corroborative report that SJL mice exposed to BPA during gestation and through the mother's milk during lactation had accelerated onset of clinical signs after infection at 4 wk of age with Theiler's virus, which produces CNS inflammation (38). At 20 wk postinfection, the degree of inflammation in the spinal cord was higher in BPA-exposed compared with vehicle treatment; no sex differences in the degree of inflammation were noted in the BPA mice.…”
Section: Discussionsupporting
confidence: 66%
“…However, (intracellular) molecular pathways often remain unknown. Many of the prenatal environmental exposures were linked to multiple different immunomodulatory outcomes and disease types. For example, BPA is associated with immunosuppression and increased infections (Menard et al, ) but has also been implicated in autoimmune diseases such as multiple sclerosis (Brinkmeyer‐Langford et al, ) and Type 1 diabetes (Bodin et al, ), and has even been associated with neuroinflammation and anxiety‐like behavior (Luo et al, ). These findings highlight the complexity of the immune system, which can be affected differently by organ, cell type, and molecular pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similar ambiguity exists for prenatal exposure to BPA. Previous discussed studies have associated prenatal BPA with autoimmunity (Bodin et al, ; Brinkmeyer‐Langford et al, ) as well as immunosuppression and increased infections (Menard et al, ). However, yet another animal study showed that prenatal exposure to BPA was dose dependently linked to a decrease in Treg cell populations (Yan, Takamoto, & Sugane, ).…”
Section: Immunomodulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic (NOD) mice given BPA during gestation generated female offspring with an increased incidence of diabetes [39]. Perinatal BPA exposure accelerated inflammation in a mouse model of virally-induced multiple sclerosis [40]. …”
Section: Bisphenol Amentioning
confidence: 99%